A Web Presence Analysis of Malaysian Government Agency Websites - Azizah, Sarkowi (2005)
Electronic government was implemented to deliver electronic services to various citizens through the websites. The presence stage and credibility of government websites is significant to reflect the reputation of each agency. Web Assessment Measure Index establish by United Nations is a standard measures used to rank the stage of official websites for every countries. This study focused on the development stage of Malaysia’s government agency websites as a projection of the implementation of e-Government project. The objectives are to identify the Malaysian government agency web presence stage, credibility factors based on the last updated period and downloading time, and the website updating problem from webmaster view. A multi-method approach was used to, such as inspection method on selected websites, URL analysis using automated web evaluation tools and e-mail survey to the webmaster. As an exploratory study, 74 government agencies website was derived from the Malaysia’s government official portal, myGovernment. The findings shows that the majority of Malaysian government website presence in Stage III to V. Many of the website did not achieves the expected quality with only 31 percent which has been updated less than once a month and 76 percent are poor in downloading times (more than 10 seconds). This research also found that ‘the difficulty to get information from others’ is the major problem that webmaster faced in many government agencies.